2017
DOI: 10.1007/s00056-016-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impacted maxillary canines on root resorption of lateral incisors

Abstract: The impacted canines caused root resorption of lateral incisors. The angulation of the canine was steeper on the labial side than on the palatal side but root resorption of adjacent laterals was not different. There were no statistically significant differences in the amount of root resorption of the laterals when the canine was evaluated according to localization and angulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 27 publications
11
31
0
Order By: Relevance
“…For gender distribution, the majority of the CBCTs were for females (78%) that were similar to the percentage reported in previous studies [2,15,17,20]. It was also consistent with what has been documented in the literature as a greater prevalence of IMC in females than in males [1,4,21]. Such difference could be attributed to the variations in genetics or overall growth and development of craniofacial structures between the two genders [11].…”
Section: Discussionsupporting
confidence: 89%
“…For gender distribution, the majority of the CBCTs were for females (78%) that were similar to the percentage reported in previous studies [2,15,17,20]. It was also consistent with what has been documented in the literature as a greater prevalence of IMC in females than in males [1,4,21]. Such difference could be attributed to the variations in genetics or overall growth and development of craniofacial structures between the two genders [11].…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have compared canines presenting with buccal and palatal impaction against control groups. 10,11,35 However, there are conflicting results. Kim et al reported that impacted maxillary canines in a buccal position caused more resorption in adjacent teeth than those in palatal positions and the relationship was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…There was, however, no noted statistical significance. 11 As these studies were conducted in different geographic regions, the differences in the results could be attributed to demographic variability as it has been previously reported that the variability of a population influences the incidence of resorption in any tooth or individual in relation to displaced maxillary canines. 13 When comparing impacted maxillary canines according to the four sectors of mesiodistal location, it was noted that the lateral incisor resorption rate increased with greater canine proximity to the maxillary midline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study (20) the angulation of the canine was steeper on the labial side than on the palatal side, but root resorption of adjacent laterals was not different. There were no statistically significant differences in the amount of root resorption of the laterals when the canine was evaluated according to localization and angulation .…”
Section: B 3d Position Of Maxillary Canine Impactions and The Influence On Adjacent Incisor Root Resorption (Tab Ii)mentioning
confidence: 91%